Sediment dynamics in the salt marshes of the Ria Formosa lagoon - Petillon, Anicet (2021)
Salt marshes are transitional environments between the ocean and the land. They are home to numerous species and provide many ecosystem services. They are regulated by various geomorphological, hydrodynamic, and biological factors. To ensure their longevity, these environments require a substantial sediment supply to maintain themselves in the intertidal zone. The objective of the study was to characterize the sediment dynamics in a marsh platform of the Ria Formosa lagoon through field campaigns, and at distinct hydrodynamic conditions (spring tides and neap tides). Hydrodynamic conditions (tidal range, hydroperiod, tidal current direction, alongshore and cross-shore current velocities) were recorded at four sampling stations, placed from the Ramalhete Channel towards the intermediate/high marsh. Suspended sediment samples were collected at the sampling stations and at varying water column depths and analysed for suspended concentrations. The deposition rates at each sampling station were also determined. The obtained results shows that dominant currents are alongshore though the cross-shore velocities become more important landward, toward the high marsh. The obtained total suspended sediment concentrations decrease along the studied transect. In contrast, sediment deposition rates increase along the transect, towards the mainland. Vegetation plays an important role in influencing hydrodynamics and sediment transport. Zostera noltei does not offer much resistance to hydrodynamic flow. During spring tides, Spartina maritima allows an increase in velocity in the lower marsh, which allows sediment to be brought into the upper marsh, which is only flooded during spring tides. Sarcocornia sp. reduces the velocity of the currents, which allows for lower energetic hydrodynamic conditions, favourable for sediment deposition. The tidal range seems to have no influence on the sediment dynamics on the tidal flat. But tidal conditions have a higher influence on the salt marsh (low marsh and high marsh).